COMPARISON OF THE EFFECTS OF DESFLURANE AND SEVOFLURANE IN AWAKENING AND COGNITIVE FUNCTION AFTER A GENERAL ANESTHESIA - Ognjanova Simjanovska, Violeta; Shirgoska, Biljana; Donev, LJupcho; Leshi, Albert; Angjusev, Darko (Department of Anaesthesia and Reanimation, Faculty of Medicine, Ss. Cyril and Methodius University in Skopje, R.N. Macedonia, 2024)
Introduction: The pharmacokinetics of desflurane and sevoflurane favour improved intraoperative control of anaesthesia and led to faster postoperative recovery. These anaesthetics have a lower blood/gas coefficient than isoflurane and halothane. (1) The low fat/gas coefficient and low brain/blood coefficient of desflurane lead to faster elimination of and faster awakening from anaesthesia. This leads to a quicker return of cognitive functions and speedier discharge from the Post Anaesthesia Care Unit (PACU). Objectives The purpose of this study is to compare the emergence time and time of return of cognitive functions in patients with general inhalation anaesthesia (general anaesthesia) maintained with inhalant anaesthetics desflurane and sevoflurane, respectively, under standardized conditions. Material and methods: This study included ASA I and II patients undergoing colorectal abdominal surgery who were randomly assigned into two groups: the first group received the inhalation anaesthetic desflurane in combination with the analgesic remifentanil for anaesthesia maintenance, while the second group was kept under using sevoflurane in combination with fentanyl. We used standard hemodynamic monitoring, the Train of Four (TOF) and the Bispectral Index System (BIS) to determine the depth of the anaesthesia. We recorded the time required for extubation, the opening of the eyes, verbal response, the modified Aldrete score of 9, the Mini Mental State Examination (ММSE) of 25 and the Short Orientation-Memory-Concentration Test (OMCT). Results: The results, expressed in minutes and obtained in both patient groups, demonstrate a significantly shorter time for regaining cognitive functions in the patients who received a desflurane inhalation anaesthetic with remifentanil compared to the patients who received a sevoflurane inhalation anaesthetic with fentanyl. This is thought to be due to the faster pharmacokinetic profile of desflurane, leading to an accelerated elimination in the patients. Desflurane, in combination with remifentanil, a short-acting opioid, further shortens the recovery time of cognitive functions. Conclusion: This study underscores that the time required for early recovery from anaesthesia is markedly shorter in patients receiving desflurane compared with patients given sevoflurane when administering general anaesthesia. This finding emphasizes the potential benefits of desflurane in optimizing perioperative outcomes, including faster emergence from anaesthesia and cognitive recovery.
Keywords: desflurane; sevoflurane; inhalational anaesthetics; opioids; cognitive function